Measurements of Patellofemoral Morphology Characteristics in Indonesian Population: an MRI Based Study - Ludwig Andre Pontoh; Ismail Hadisoebroto Dilogo; Achmad Fauzi Kamal; Wahyu Widodo; Sholahuddin Rhatomy; Jessica Fiolin (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Patellar malalignment is the imbalance relationship between patella and trochlea, in which clinical findings most of the time are obscured; hence diagnosis is often challenging. Magnetic resonance imaging (MRI) is the most sensitive tool to detect subtle patellar malalignment features, so diagnosis can be made early. However, there has been no clear consensus on the normal value of patella morphology until today. This study aims to determine patellofemoral morphology values in Indonesian using MRI. This was a retrospective study of 202 patients aged 18-40 years old with knee problems without patellar instability. Patellar morphology parameters including Insal Savati ratio (IS ratio), patellar tilt angle (PTA), sulcus angle (SA) and tibial tubercle-trochlear groove distance    (TT-TG) were evaluated and recorded for statistical analysis. There was no significant correlation between anthropometric values and patellar morphology values. There were significantly higher PTA, SA and TT-TG values in females compared to males. The mean value of the IS ratio in the Asian population using MRI was 0.99 ± 0.14, PTA was 9.09 ± 6.88, SA was 139.20 ± 6.38, and TT-TG distance was 8.00 ± 5.25. Further studies with larger samples and multi-center results are required.